(3JMaI GdYHGO hCOdI GdChQGOs - (3CHh GdHTQi YHO GdQMef Hf Jbi GdOjf CHh HcQ Hf OGhO GdbGQis; (3CHh HcQ Hf OGhO GdMfHdj GdUGdMj GdbGOQj, Jbj GdOjf CHh GdUaG,J (B806 (3g` s
(3ChdgG (B:s
(3CeG HYO abO cfJ LeYJ ChQGO Gdjhe hGddjdI hGdCSHhY GdJi , QJHgG hGdOi bOei Gddg JYGdi QhMg hCKGHg GdLfI s
(3BNQgG (B:s
(3heLjH ef OYGc Je cJGH JMaI GdYHGO hCOdI GdChQGO s
(3GdfSNI HgG MhGTs
(3TQM ajg GdeDda ChQGO hGdOg GdeSeGI HGdOQ GdefJbGg GdeQahYs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
(3GdRGhjI GdMeRGhjI (B- (3GdeZQH (B(101) s
Keywords: (3GdJUha hGdBOGH GdTQYjIs